EFEK MOTIVASI INTRINSIK DARI STRATEGI ELEMEN GAMIFIKASI PEMBELAJARAN - Febriansah, Aris Triwahyu; Syifa’ul Qolbi, Muhammad; Soepriyanto, Yerry; Purnomo, Purnomo (STKIP PGRI Situbondo, 2024)
This study aims to examine and analyze the differences in intrinsic motivation of learners based on Point+Leaderboard (PL) and Point+Badge (PB) gamification element strategies. The research sample was 84 undergraduate students of the Department of Educational Technology, State University of Malang. Data was collected using the Intrinsic Motivation Inventory (IMI) questionnaire which consists of 4 variables: interest/enjoyment (EJ), perceived competence (PC), effort (EF), and pressure (PR). The research method used the Independent T-Test to test the difference in intrinsic motivation between OT and PB groups. The t-test results showed significant differences in EJ and EF variables between OT and PB groups. This shows that PL is more effective in increasing learners' enjoyment/interest and effort compared to PB. However, there is no significant difference in PC and PR variables between OT and PB groups. This means that both PL and PB are equally able to give positive effects on the sense of competence and do not cause negative effects on learners' stress. This study shows that Point+Leaderboard strategy is more effective in increasing learners' intrinsic motivation compared to Point+Badge strategy